Dampak Psikologis Rasionalisasi Pernikahan Dini pada Remaja di Desa Bancamara Kabupaten Sumenep - Suryanto, Totok Agus; Ayu, Filzah (Medan Resource Center, 2023)
Early marriage in Bancamara Village is prevalent, and its rationalization is deeply ingrained in the community due to economic, parental, cultural, and traditional reasons. This study explores the psychological impact of rationalizing early marriage in Bancamara Dungkek Sumenep Village using a qualitative field research approach. Interviews, observations, and documentation were used as data collection methods, and the subjects included officials from the KUA, Village Head, community members, and youth. The findings indicate that early marriage is widely accepted, supported, and considered a natural practice in the village. However, it has negative consequences on adolescents, leading to anxiety and unpreparedness. Early married teenagers experience fear and worry when facing challenges within their families.